UJI DAYA HAMBAT ANTIBAKTERI KOMBINASI EKSTRAK DAUN PEPAYA ( Carica papaya L. ) DENGAN DAUN SIRIH ( Piper betle L. ) TERHADAP BAKTERI Staphylococcus aureus - Amy Siska Zulyani; Samsuar Samsuar; Yuli Wahyu Tri Mulyani; Muti Dianda Sari (Program Studi Farmasi Universitas Tulang Bawang, 2022)
Infection is a disease that is often found in Indonesia. Infectious diseases can be caused by one of the gram-positive bacteria, staphylococcus aureus bacteria. How to prevent infectious diseases is to inhibit the growth of Staphylococcus aureus bacteria. Papaya leaf plant (Carica papaya L.) and betel leaf plant (Piper betle L.) is a plant that has long been used by the community as a traditional medicine that can cure diseases, one of which is as an antibacterial. This study aims to find out the antibacterial bland power of the combination of papaya leaf extract with betel leaves in inhibiting Staphylococcus aureus bacteria. The method used is an experimental method of combining the concentration of papaya leaf extract with betel leaves, namely K1 (100%+0%), K2 (30%+70%), K3 (40%+60%), K4 (50%+50%), K5 (60%+40%), K6 (70%+30%), K7 (0%+100%), K (-) Aquadest, K(+) Chloramfenikol, which then concentrates on testing Staphylococcus aureus bacteria with the welling method. The variables measured in this study are the diameter of the bland zone. The observations were analyzed using one away anova with a sig (0.00) < A value (0.05) continued with Tukey that showed all treatments were different. This study can be concluded that the combination of papaya leaf extract with betel leaf proved to have a bland force of antibacterial activity against Staphylococcus aureus bacteria with the largest bland zone in K2 (papaya leaf extract 30% + 70% betel leaf extract) with an average diameter of 12.17 mm. Keywords: papaya leaves, betel leaves, infections, Staphylococcus aureus, bland zone.